2020
DOI: 10.1186/s40462-020-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Stopover departure decisions in songbirds: do long-distance migrants depart earlier and more independently of weather conditions than medium-distance migrants?

Abstract: Background Songbirds following distinct migration strategies (e.g. long- vs. short- to medium-distance migrants) often differ in their speed of migration during autumn and, thus, are assumed to face different time constraints. During migration, most songbird species alternate migratory flights with stopover periods. Many of them restrict these migratory flights to the night, i.e., they are nocturnal migrants. At stopover, nocturnal migrants need to select a specific night (night-to-night decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 58 publications
11
97
3
Order By: Relevance
“…Yet, the occurrence of IMN in late autumn and early spring and the observed differences in airspeeds between IMN and WMN in autumn (Table 1) imply that different species might be involved in migration on different nights. IMN in our study may reflect predominantly short-distance migrants who have been shown to respond differently to weather conditions at departure than long-distance migrants in a comparative analysis of several songbird species (Packmor et al 2020). Currently, due to the limitations of the radar system and the similar distributions of airspeeds between seasons we cannot determine whether species composition differs between spring and autumn.…”
Section: Discussionmentioning
confidence: 79%
“…Yet, the occurrence of IMN in late autumn and early spring and the observed differences in airspeeds between IMN and WMN in autumn (Table 1) imply that different species might be involved in migration on different nights. IMN in our study may reflect predominantly short-distance migrants who have been shown to respond differently to weather conditions at departure than long-distance migrants in a comparative analysis of several songbird species (Packmor et al 2020). Currently, due to the limitations of the radar system and the similar distributions of airspeeds between seasons we cannot determine whether species composition differs between spring and autumn.…”
Section: Discussionmentioning
confidence: 79%
“…This feature may prove particularly useful in follow up studies that aim at linking movements and stop-overs to geographical features or short, intense weather events. In addition, our quantitative estimation of bird’s take-off would also nicely complement studies on species-specific variations in the timing of take-off as retrieved from individual tracking (Müller, Eikenaar, Crysler, Taylor, & Schmaljohann, 2018; Packmor, Klinner, Woodworth, Eikenaar, & Schmaljohann, 2020), and shed new light into the variation in landing behaviour.…”
Section: Discussionmentioning
confidence: 85%
“…While we do not have information on the species in our study, the timing of these nights suggests that they may be generally representative of short to medium distance migrants in the region. Packmor et al (2020) for example showed that night to night departure decisions of a short and medium distance migratory passerine was influenced by tailwinds and change in barometric pressure, while these weather factors did not influence departure decisions of a long distance migrants. However, in order to determine whether differential response to weather among and perhaps even within species results in peak migration over the North Sea occurring predominantly in early spring or late autumn requires further research integrating information on fluxes, species composition and regional synoptic conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, the passage of high-pressure systems can be related to opposing winds in autumn and supporting winds in spring (Dokter et al, 2013). Additionally, species with similar flight modes but contrasting migration strategies, for example short vs long distance passerines may respond differently to weather conditions at departure (Packmor et al, 2020). As many weather variables are closely intercorrelated, less influential variables such as the relative humidity will tend to vary in predictable ways as a function of the variables of higher importance, such as the pressure systems (Richardson, 1990), or precipitation, especially during relatively unstable atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%